Cytotoxic activities of arundina graminifolia sp. extracts on HEPG2 liver cancer cell - Mohamad Ali, Anisah (2015)
Orchids scientifically known as Orchidaceous is a unique plant that have a lot of uses especially in developing modem drug nowadays including one of its species, Arundina Graminifolia. It is easily found and most distributed in southern China, India, from Himalaya to Burma and Indonesia. A new research found that the main component of this plant has higher potency and can be used in developing cytotoxic drug. Therefore, this research is conducted to discover the cytotoxic activity of A. graminifolia with its side effect and their reliability with scientific medicine. Thus, the amount of concentration that produced cytotoxic activity can be identified. In evaluating the cytotoxic activity of this plant, the extract compounds from different parts of A. graminifolia are tested on cancer and normal liver cell and compared their IC50 value with scientific drug which is Doxorubicin. Through the research, two types of extracts which are natural and in vitro A. graminifolia sp. are prepared in investigating the cytotoxic effect against HEPG2 liver cancer cell and WRL68 normal liver cell. Each plant are divided into three parts which are leaves, stem and root with variety of concentration range from 1 to 0.0001 mg/ml. the evaluation of the cytotoxicity is based on the IC50 value which is compared to the US NCI value. Based on the result collected, the root part of natural plant shows strong cytotoxic effect with gives IC50 value 27.54 µg/ml. further studies are recommended for detailed and extensive biological compound involve in cytotoxicity of this plant.